An empirical assessment of global capital productivity - Julia Knolle; Kai Lehmann (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2016)
Does the world experience a secular decline in capital productivity? Due to the long-run downward trend in interest rates, some economists do think so. However, this reasoning equates capital productivity with interest, which is a critical assumption. This paper presents a new proxy that can be used to estimate capital productivity. It is based on weighted average cost of capital (WACC), which are employed by firms in their investment appraisals as a benchmark return. The paper uses an original WACC data set for many OECD countries and for the time period 2000-2015. Data are adjusted for tax distortions and expected inflation. The principle finding is that the data do not indicate a long-run decline in capital productivity.
Keywords: D24; E22; E43; 330; capital productivity; cost of capital; interest-growth-differential; WACC